\( \int ( \frac { 2 } { x ^ { 6 } } + 7 - \frac { 6 } { x ^ { 2 } } ) d x = \square \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To solve the integral \( \int \left( \frac{2}{x^6} + 7 - \frac{6}{x^2} \right) dx \), we can break it down into simpler parts: 1. For \( \frac{2}{x^6} \), we can write it as \( 2x^{-6} \). The integral becomes: \[ \int 2x^{-6} \, dx = 2 \cdot \frac{x^{-5}}{-5} = -\frac{2}{5x^5} \] 2. The integral of the constant 7 is: \[ \int 7 \, dx = 7x \] 3. For \( -\frac{6}{x^2} \), we write it as \( -6x^{-2} \): \[ \int -6x^{-2} \, dx = -6 \cdot \frac{x^{-1}}{-1} = 6x^{-1} = \frac{6}{x} \] Now we can combine all of these results: \[ \int \left( \frac{2}{x^6} + 7 - \frac{6}{x^2} \right) dx = -\frac{2}{5x^5} + 7x + \frac{6}{x} + C \] So, the final answer is: \[ -\frac{2}{5x^5} + 7x + \frac{6}{x} + C \]